Delimitação da responsabilização civil socioambiental das instituições financeiras no Direito brasileiro e no Direito comparado - Bernal, Rafaela Moraes (2021)
This paper aims at studying the issue of the financial institutions’ social-environmental civil liability as indirect polluter by analyzing their concepts, theories of risk and casual link, including those which would be more appropriate to those that do not directly cause any harm (the indirect polluter) when following parameters that use vigilance duties. In this way we ensure greater effectiveness when protecting social and environmental aspects. There is a risk of causing unbounded liability for financial institutions, even in cases where such funding is disbursed in compliance with national, state, and local law self-regulations - and international standards. This not only increases the cost of credit but also makes environmental protection less efficient. The present study analyzes only the funding of activities that pose a social and environmental risk when it is obvious that the financial institution does not act according to its surveillance duties. This establishes a causal link between the management of the financial institution and the environmental damage it causes. Thus, the financial institution inserts itself in the list of indirect polluters and subjects itself to the civil environmental responsibility rules adopted by the Brazilian law ordinance, based on the theory of risk and the theory of direct and immediate consequences